Symposium 1: Working Together: Perceptions of the Role of the Tutor in a Postgraduate Online Learning Programme - Sherratt, Cathy (Proceedings of the International Conference on Networked Learning, 2008)
This paper will report the latest phase of an ongoing programme of work in progress, exploring online learning in a part-time postgraduate programme in Clinical Education at Edge Hill University. The programme is delivered by means of Supported Online Learning (also known as 'blended-learning'). The focus of the current study is the Postgraduate Certificate in Teaching and Learning in Clinical Practice (PGCTLCP). The aim of this current research is to obtain insights into the perceptions and experiences of tutors and students regarding the role of the tutor within the context of the online learning environment, and to identify the influence of the tutor on the development of dialogue in the online discussion board. Semi-structured interviews were conducted with participants from a single cohort from the Postgraduate Certificate in Teaching and Learning in Clinical Practice (PGCTLCP), to establish their perceptions and expectations of tutors online, and their actual experiences of interaction with the tutors and with other students and 'peer facilitators'. For most of the students, this was also their initial experience of online learning, such that their expectations were not influenced by previous experience or involvement in different courses elsewhere. To give an added dimension, information was also gathered from the five tutors who were involved in delivering this programme to the specified cohort of students. Objective observations and analyses were also carried out on the archives of online discussion for the chosen cohort. In particular, the type of online interaction was explored, using a Typology of Online Responses to identify where 'dialogue' actually takes place, as opposed to a series of unconnected statements or monologues, which can often be seen to occur in online discussion boards everywhere, but which are deemed by the PGCTLCP Course Team to be less satisfactory as learning experiences. The tutors' styles of facilitation and intervention were also identified using a simple taxonomy. Preliminary analysis of the interviews with tutors and students is presented in this paper, along with an initial analysis of the actual postings from the course discussion board. The mechanisms involved in achieving a full and rich dialogue in an online discussion board appear to be complex, and as yet not fully understood, although some scope has already been identified for the potential of tutors to influence this process. Previous work suggests that online discussion boards benefit from not being overly tutor-focused, and we also identified that the actions of individual participants in taking on the facilitative role can also be significant, and can create a different dynamic than facilitative intervention by a tutor. Initial findings in this current study indicate that the concept of tutor 'presence' is widely acknowledged to be important, both by students and by tutors. However, early indications suggest that different individuals perceive both the nature and practice of 'facilitation' differently. It is also suggested that different individuals perceive different levels of intervention as desirable. The challenge, therefore, is when and how the tutor should intervene in order to achieve optimum engagement by all participants. Implications for course design and tutor intervention will be discussed, along with a consideration of future work.